Android-based capacitor discharging calculator application - Wisnu Kartika; Erika Loniza; Meilia Safitri (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Nowadays, many people using smartphone to connet to her colleague. The electronic device using capacitor and transistor. The electronic device’s size recently become smaller. The capacitor can be used to the most important function that is used to store the energy and on the DC system is used to decrease the ripple from AC source. This research purpose build an apps which can calculate the charge remaining inside the capacitor. The method is using RC time constant. This research work well and can work functionally.